Penerapan Weighted Sum Model (WSM) Dalam Penentuan Peserta Jaminan Kesehatan Masyarakat - Mesran Mesran; Suginam Suginam; Surya Darma Nasution; Andsyah Putera Utama Siahaan (STIKOM Tunas Bangsa Pematangsiantar, 2017)
Community Health Insurance is one of the government programs for the people of Indonesia in obtaining treatment services at Puskesmas. The program is very helpful for people who are low income and live below the poverty line. Indicators for the government in providing this service consists of 10 (ten) criteria that are House Ownership Status, Floor Area per Household Member, Type of Floor of House, Type of Wall House, Lighting House Used, Fuel Used, Frequency Of Eating In A Day, Ability Buy meat/chicken/milk in a week, Employment of head of household, Education of head of household. In the application, of course, has constraints in deciding who the participants who get the Jamkesmas service. With the application of one of Multi-Criteria Decision Making (MCDM) able to overcome obstacles faced by government. Some methods of MCDM such as Simple Additive Weighting(SAW), Weighted Product(WP), Weighted Sum Model(WSM) can solve this problem. By applying the WSM is relatively easy and fast, is believed to be able to get the best results.